(3GdRHOI aj TQM bUjOI GdHQOIs - (3GdLQLGhj GdCRgQj GdeUQj, Rjf GdOjf, GdhbGO, NGdO Hf YHO Gddg Hf CHj HcQ, J (B905 (3g`s ((3GdMGL CMeO Hf GdMGL SdjeGf CMO Hfj GdTjN YdhGfs)
(3ChdgG (B:s
(3CeG HYO MeOG ddgajbhd GdYHO GdabjQ Edi ehdGg GdZfj NGdO Hf YHO Gddg GdCRgQj bO SCdJfj CjgG GdCN GdfLjM Cf CVY TQMG dWjaG Ydi HQOI GdeOjM ddTjN GdEeGe TQa GdOjf eMeO GdHhUjQjs
(3BNQgG (B:s
(3Efc MejO eLjO RfI YQTc hQVi faSc heOGO cdeGJc CaVd UdhGJc YOO eYdheGJc cdeG PcQc GdPGcQhf hZad Yf PcQc GdZGadhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 297s
(3eYLe GdeDdajf(B: 1 / 668s
(3cTa GdXfhf(B: 2 / 1332s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs